How gender norms and 'good girl' notions prevent adolescent girls and young women from engaging with PrEP: qualitative insights from Zimbabwe - Morten Skovdal; Camilla Lysemose Clausen; Phyllis Magoge-Mandizvidza; Freedom Dzamatira; Rufurwokuda Maswera; Rangarirayi Primrose Nyamwanza; Constance Nyamukapa; Ranjeeta Thomas; Simon Gregson (BMC, 2022)
Abstract Background Pre-exposure prophylaxis, or PrEP, has been hailed for its promise to provide women with user-control. However, gender-specific challenges undermining PrEP use are beginning to emerge. We explore the role of gender norms in shaping adolescent girls and young women's (AGYW) engagement with PrEP. Methods We draw on qualitative data from 12 individual interviews and three focus group discussions with AGYW from eastern Zimbabwe. Interviews were transcribed and thematically coded in NVivo 12. Emerging themes were further investigated using Connell's notion of 'emphasised femininity'. Results Participants alluded to the patriarchal society they are part of, with 'good girl' notions subjecting them to direct and indirect social control. These controls manifest themselves through the anticipation of intersecting sexuality- and PrEP-related stigmas, discouraging AGYW from engaging with PrEP. AGYW recounted the need for permission to engage with PrEP, forcing them to consider engaging with PrEP in secrecy. In addition, limited privacy at home, and fear of disclosure of their health clinic visits, further heightened their fear of engaging with PrEP. PrEP is not simply a user-controlled HIV prevention method, but deeply entrenched within public gender orders. Conclusion AGYW face significant limitations in their autonomy to initiate and engage with PrEP. Those considering PrEP face the dilemma of Scylla and Charybdis: The social risks of stigmatisation or risks of HIV acquisition. Efforts to make PrEP available must form part of a combination of social and structural interventions that challenge harmful gender norms.